MR imaging of the ectopic bright signal of posterior pituitary regeneration. - el Gammal, T; Brooks, B S; Hoffman, W H (American Journal of Neuroradiology, 1989)
High-field-strength MR studies of 13 patients with sellar and/or parasellar tumors revealed an aberrant location of the posterior pituitary bright signal in the hypothalamus in seven cases and in relation to the pituitary infundibulum in six cases. Five of the MR studies were obtained in patients who had not had surgery and had pituitary adenomas producing compression and/or destruction of the posterior lobe. In the other eight cases, the aberrant bright signal occurred after hypophysectomy in seven patients and after removal of a craniopharyngioma in the eighth. Accumulation of neurosecretory material and regeneration of pituitary tissue in these ectopic locations have been documented previously in animal experiments and in a few reports in humans after hypophysectomy. MR imaging now provides further corroborative evidence in vivo of this process in which a "miniature posterior lobe" is formed.